2021
DOI: 10.3389/fpsyg.2020.574403
|View full text |Cite
|
Sign up to set email alerts
|

Song Morphing by Humpback Whales: Cultural or Epiphenomenal?

Abstract: Singing humpback whales (Megaptera noavaengliae) collectively and progressively change the sounds and patterns they produce within their songs throughout their lives. The dynamic modifications that humpback whales make to their songs are often cited as an impressive example of cultural transmission through vocal learning in a non-human. Some elements of song change challenge this interpretation, however, including: (1) singers often incrementally and progressively morph phrases within and across songs as time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Thus, this quantitative approach using the LSI resulted in a shortcoming of identified linkages. Additionally, the delineation process of humpback whale song remains highly subjective (Cholewiak et al, 2013;Mercado, 2021). Although the protocol on how to delineate and measure phrases defined by Cholewiak et al (2013) was followed in the present study, the acceptable level of variability within the classification procedure has a large subjective component (Mercado, 2021), making comparisons between studies difficult.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, this quantitative approach using the LSI resulted in a shortcoming of identified linkages. Additionally, the delineation process of humpback whale song remains highly subjective (Cholewiak et al, 2013;Mercado, 2021). Although the protocol on how to delineate and measure phrases defined by Cholewiak et al (2013) was followed in the present study, the acceptable level of variability within the classification procedure has a large subjective component (Mercado, 2021), making comparisons between studies difficult.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the delineation process of humpback whale song remains highly subjective (Cholewiak et al, 2013;Mercado, 2021). Although the protocol on how to delineate and measure phrases defined by Cholewiak et al (2013) was followed in the present study, the acceptable level of variability within the classification procedure has a large subjective component (Mercado, 2021), making comparisons between studies difficult. Yet, a combined qualitative and quantitative assessment as applied in the present study has been suggested to produce more robust results (Garland et al, 2013b).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When the acoustic changes that singing humpback whales make to their songs over time are taken into account, a different picture of how singers modify their songs emerges (Mercado, 2022). Acoustic analyses of humpback whale songs show that the changes singers make to units and phrases across years are comparable to the changes they make within and across consecutive songs (Mercado, 2021; Mercado & Perazio, 2021; Payne & Guinee, 1983). Those transformations involve: (1) the compression/expansion of unit durations, (2) shifts in unit frequency content and frequency modulation, and (3) increases/decreases in the number of unit/phrase repetitions (Mercado, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Each of these populations has its own song type, but song types that are found in one population tend to be picked up by others to the east in later years [38]. Some authors suggest that humpback whales may have a finite number of song elements that they recombine through usage learning [40][41][42] but considering the gradual changes in song types especially in the Northern Hemisphere, vocal production learning seems to be a more likely explanation for the changes observed.…”
Section: Cetaceansmentioning
confidence: 99%